Effect of various processing methods on the interfacial reactions in SiCp 2024 Al composites - Lee, JC; Byun, JY; Oh, CS; Seok, HK; Lee, HI (PERGAMON-ELSEVIER SCIENCE LTD, 1997)
SiCp/2024 Al composites were prepared using various processing techniques, such as spray forming, powder metallurgical hot pressing, thixoforming, and compocasting. The interfacial characterizations of these composites were performed using scanning electron microscopy, Auger electron spectrometry, transmission electron microscopy, and X-ray diffraction on reaction products extracted using the electrochemical dissolution. The value of these combined techniques in elucidating the morphologies of the interfacial reaction products was also demonstrated. The influence that each fabrication process has on the extent of the interfacial reaction was studied. Adequate process parameters to fabricate SiCp/Al alloy composites were proposed based on thermodynamic considerations. (C) 1997 Acta Metallurgica Inc.
Keywords: SILICON-CARBIDE; ALUMINUM; ALLOYS; SYSTEM